Recent advances of interfacial modification over tantalum nitride photoanodes for solar water oxidation: a mini review - Wang, Pengpeng; Than Oo, Aman Maung; Chen, Liangji; Zhang, Doudou (Frontiers in Chemistry, 2025)
Photoelectrocatalytic (PEC) water splitting represents a highly ideal approach for the efficient conversion of solar energy into sustainable green hydrogen. Although tantalum nitride (Ta3N5) has emerged as a promising photoanode material, its performance is far below the theoretical limit. Among several photoelectrode design strategies, interfacial modification can be beneficial for suppressing interfacial charge recombination and promoting charge transfer process, which is a key focus in recent research. In the review, a brief overview of recent advances in interfacial modification strategies for Ta3N5 photoanodes and their influence on the structure-performance relationship are summarized, aiming at an in-depth understanding of the charge-transfer mechanism during PEC water oxidation, and providing insights into designing efficient and stable Ta3N5 photoanodes for solar-to-fuel conversion through photoelectrocatalysis.